Interhemispheric and Intrahemispheric Connectivity From the Left Pars Opercularis Within the Language Network Is Modulated by Transcranial Stimulation in Healthy Subjects - Yoo, Woo-Kyoung; Vernet, Marine; Kim, Jung-Hoon; Brem, Anna-Katharine; Bashir, Shahid; Ifert-Miller, Fritz; Im, Chang-Hwan; Eldaief, Mark; Pascual-Leone, Alvaro (Frontiers in Human Neuroscience, 2020)
Neural activity related to language can be modulated within widespread networks following learning or in response to disruption including the experimental application of non-invasive brain stimulation. However, the spatio-temporal characteristics of such modulation remain insufficiently explored. The present study combined transcranial magnetic stimulation (TMS) and EEG to explore the modulation of activity across the language network following continuous theta burst stimulation (cTBS) of the left pars opercularis. In ten healthy subjects (4 females), neuro-navigated cTBS was delivered over the left pars opercularis of the frontal operculum (part of the traditional Broca’s area) at 80% of active motor threshold stimulation intensity. Real cTBS and sham cTBS were performed in two different visits separated by at least 48 hours. Before, immediately, and 10 min after cTBS, 30 single pulses of TMS were delivered to the left pars opercularis at 80% of the resting motor threshold while EEG was simultaneously recorded. We examined the cTBS-induced modulation of phase locking values (PLV) between the TMS-evoked potentials (TEPs) recorded over the pars opercularis and those recorded over its right-hemispheric homologue area, the left supramarginal area, and the left superior temporal area in different EEG frequency bands and different time windows following cTBS. cTBS to the left pars opercularis induced within the gamma band: (1) a significant increase in TEP phase synchronization between the left and right pars opercularis at an early time window (250-350 ms) following cTBS; and (2) significantly increased PLV with the left supramarginal area and the left superior temporal area at a later time window (600-700 ms). In the theta and delta-band, cTBS to the left pars opercularis induced significantly increased phase synchronization of TEPs between the left pars opercularis and the posterior left hemispheric language areas at a late time window. In sham condition, there was a significant decrease in TEP phase synchronization of the high beta band between left pars opercularis and left superior temporal area at 200-300 ms. These results contribute to characterize the dynamics of the language network and may have implications in the development of non-invasive stimulation protocols to promote the language rehabilitation in aphasia patients.